On the Structural Approach to Social Representations (2005)
The theory of social representations is one of the most vigorous areas in social psychology. Far from constituting a homogeneous body of knowledge, the theory consists of several analytical perspectives, including the structural approach. In this paper I propose that most of the assumptions of the structural approach applied to social representations or the central core theory are grounded in traditional conceptions of social cognition and mental representations, which are at variance with the general theory. The fact that one can view the structural approach embedded within associative networks and schema models makes it similar to most theories of attitude structure. Since the structural approach has remained within a mentalist social cognition paradigm, this paper proposes to move it towards a theory of social cognition that reflects the sociocultural conditions of creation and transformation of thought, and then emphasizes the communicative and ideological components of social life. © 2005, Sage Publications. All rights reserved.